MiRNA profiling of primate cervicovaginal lavage and extracellular vesicles reveals miR‐186‐5p as a potential antiretroviral factor in macrophages. Issue 10 (11th September 2020) - Zhao, Zezhou; Muth, Dillon C.; Mulka, Kathleen; Liao, Zhaohao; Powell, Bonita H.; Hancock, Grace V.; Metcalf Pate, Kelly A.; Witwer, Kenneth W.
Abstract : Cervicovaginal secretions, or their components collected, are referred to as cervicovaginal lavage (CVL). CVL constituents have utility as biomarkers and play protective roles in wound healing and against HIV‐1 infection. However, several components of cervicovaginal fluids are less well understood, such as extracellular RNAs and their carriers, for example, extracellular vesicles (EVs). EVs comprise a wide array of double‐leaflet membrane extracellular particles and range in diameter from 30 nm to over one micron. The aim of this study was to determine whether differentially regulated CVL microRNAs (miRNAs) might influence retrovirus replication. To this end, we characterized EVs and miRNAs of primate CVL during the menstrual cycle and simian immunodeficiency virus (SIV) infection of macaques. EVs were enriched by stepped ultracentrifugation, and miRNA profiles were assessed with a medium‐throughput stem‐loop/hydrolysis probe qPCR platform. Whereas hormone cycling was abnormal in infected subjects, EV concentration correlated with progesterone concentration in uninfected subjects. miRNAs were present predominantly in the EV‐depleted CVL supernatant. Only a small number of CVL miRNAs changed during the menstrual cycle or SIV infection, for example, miR‐186‐5p, which was depleted in retroviral infection. This miRNA inhibited HIV replication in infected macrophages in vitro . In silico target prediction and pathway enrichment analyses shed light on the probable functions of miR‐186‐5p in hindering HIV infections via immunoregulation, T‐cell regulation, disruption of viral pathways, etc. These results provide further evidence for the potential of EVs and small RNAs as biomarkers or effectors of disease processes in the reproductive tract. Abstract : By comparing the microRNA and extracellular vesicle profiles of cervicovaginal lavage of both uninfected and infected macaques, we observed an enrichment of microRNAs in extracellular vesicle‐depleted supernatant and discovered a significant reduction in miR‐186‐5p after simian immunodeficiency virus infection. Furthermore, once transfected into HIV‐infected human macrophages, synthetic miR‐186‐5p mimics inhibited HIV replication, demonstrating its antiretroviral potential.